The complete chloroplast genome of Torilis scabra (Apiaceae) - Xue-Ying Yao; Zhi-Xiang Chen; Qi-Zhi Wang (Mitochondrial DNA. Part B. Resources, 2019)
Torilis scabra (Thunb.) DC. is widely distributed in China and Japan and has been introduced to North America. In this study, the complete chloroplast genome sequence of the T. scabra was obtained by de novo assembly using the NGS data. The chloroplast genome of T. scabra was 157,855 bp in length and divided into four distinct regions, such as large single-copy region (85,362 bp), small single-copy region (17,993 bp), and a pair of inverted repeat regions (27,250 bp). The genome annotation predicted a total of 127 genes, including 82 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenetic analysis with reported chloroplast genomes showed that T. scabra has a close genetic relationship with Anthriscus cerefolium.